Utilizing team-based project research in improving scientific thinking skills among social studies students in higher education - Nuansa Bayu Segara; Silvi Nur Afifah; Ubong Imang; Wiwik Sri Utami; Agung Dwi Bahtiar El Rizaq (Universitepark Publishing Ltd, 2025)
Scientific thinking is a critical competency for navigating the complexities of the global era, requiring the application of scientific methods to understand, analyze, and evaluate diverse phenomena and problems. This study examines the effectiveness of Team-Based Project Research (TBPR) in enhancing scientific thinking skills among students of the Social Studies Education program at the State University of Surabaya. A quantitative time-series experimental design was employed. Data were collected through questionnaires and analyzed using t-tests and ANOVA to test the hypotheses. The findings indicate that: (1) TBPR provides a systematic conceptual framework that supports pedagogical objectives through a structured sequence of research phases, ranging from problem identification to data analysis and reflection; (2) the implementation of TBPR significantly enhances students’ scientific thinking skills in higher education; and (3) TBPR functions as an effective instructional model that promotes active knowledge construction, collaborative learning, and the development of higher-order scientific reasoning. These results suggest that higher education institutions should adopt and further refine TBPR to strengthen students’ scientific thinking abilities and collaborative research competencies.